Aplicação de derivados de quitosana como agentes de transfecção para transferência gênica não viral - Picola, Isadora Pfeifer Dalla [UNESP] (2013)
One possible strategy to improve the efficiency of chitosan as a non viral vector is the modification on the polycation with the additions of hydrophilic, pH-sensitive and selective groups for the target cells, without interfering with the biological properties of chitosan, such as biodegradability and low toxicity. On this matter, the present thesis aimed the modification on the structure of chitosan, with phosphorylcholine (PC), diethylaminoethyl (DEAE) and the ligand folate (FA). Chitosan derivatives with different proportions of PC and DEAE groups were synthesized and characterized using 1H-NMR, conductimetric titration, gel permeation chromatography and UV-vis spectroscopy. The derivatives were used to prepare polyplexes with plasmid VR1412 and small interference RNA, siRNA-SSB. The particles were characterized by dynamic light scattering, resulting in nanoparticles with diameters ranging from 100 nm to 700 nm, and the zeta potential values from -25 mV to +22 mV dependent on the degree of substitution of PC and DEAE. The colloidal stability of these particles and integrity of the plasmid were verified with agarose gel electrophoresis, observing improved stability with higher N/P ratio (N = amine groups from polycation / P = phosphate groups from pDNA or siRNA), molecular weight of polymers and substitution of DEAE group. HeLa cells were used to analyze the cytotoxicity of polyplexes and polymers, as well as the transfection efficiency. The results showed that the cytotoxicity of the derivatives increases with the degree of substitution of DEAE. However, the composition can be controlled, and all the derivatives were less toxic than lipofectamine, a general commercial lipid used for gene transfer. Transfection efficiency was highly enhanced with the modifications, arrising to eight times more efficient than unmodified deacetylated chitosan and very close to the results observed for lipofectamine. The results evidenced that changes on ...